The use of conceptual map in reading comprehension for dental students according to learning styles - Quinto Márquez, Zeira (2015)
Objective: the aim of the study was to determine whether the use of conceptual map CmapTools encourages reading comprehension of expository text in dental students according to learning styles. Methodology: A quasi-experimental study with pretest and posttest in 50 students from Universidad Nacional Mayor de San Marcos was performed. Learning styles were classified with the questionnaire Honey-Alonso Learning Styles (CHAEA), the level of reading comprehension was determined using the reading comprehension predesigned test and the evaluation of the conceptual map content using Miller- Cañas semantic rubric 2008. Results: The comparisons of pretest and posttest of reading comprehension achieved an average score for the total sample of 7.5 increasing to 9.3 being favored the reflective and theoretical learning styles. The evaluation semantics of the conceptual map went from 4,5 to 9,1 points, here all the styles were favored. Conclusion: it is recognized the importance of using the conceptual map in superior education as part of the improvement of the students´ reading comprehension.